Tuning the Mechanical and Adsorption Properties of Silica with Graphene Oxide. Issue 10 (30th July 2014) - Singh, Vivek K.; Cura, M. Erkin; Liu, Xuwen; Johansson, Leena‐Sisko; Ge, Yanling; Hannula, Simo‐Pekka
Abstract Silica and graphene oxide (GO) were synthesized by modified Stöber and Hummer's methods, respectively. Silica/GO composite powders of different compositions were obtained by introduction of GO sheets in between silica particles through a hydrothermal synthesis. Composites were characterized by Fourier transform infrared spectroscopy, X‐ray diffraction analysis, and scanning and transmission electron microscopy. Density measurements were performed with a pycnometer and chemical analyses of powders were performed by energy‐dispersive X‐ray and X‐ray photoelectron spectroscopies. Composite powders showed an improvement in the Cu2+ ion adsorption property relative to pure silica. Composite powders were further consolidated at 1200 °C under 50 MPa pressure in vacuum by pulsed electric current sintering. Transparency in the UV/Vis region, the electrical conductivity, and the toughness of consolidated samples were altered by varying the GO content in the starting materials. Studies suggest that the use of GO as a reinforcing agent not only improves the mechanical properties of transparent silica ceramic, but also improves the electrical conductivity and adsorption properties of silica.